Análise da fibrose do tecido adiposo de mulheres submetidas à abdominoplastia e cirurgia bariátrica - Castro, Eduardo José Passamai de (2014)
Fibrosis is an exceeding accumulation of extracellular matrix, resulting from an unbalance between the synthesis and degradation of its components. It is associated with the metabolic alterations in the adipose tissue, however, its occurrence in the different deposits and clinical repercussions are not yet fully understood. The study aims at assessing fibrosis in the adipose tissue regarding the presence of obesity, location of the deposit [subcutaneous abdominal adipose tissue (SAAT) and the visceral one (VAT)] and its association with clinical variables. Samples of fat from SAAT and VAT were obtained from 21 women undergoing bariatric surgery (IMC>40kg/m²) and 25 VAT samples from the ones undergoing abdominoplasty (IMV<30kg/m²). The samples were processed for conventional histology. The red stain picrosirius was used to evaluate the total collagen fibers. The pictures obtained were analyzed in ADIPOSOFT®. The fibrosis percentage found in SAAT and VAT were analyzed through non-parametric static tests, using the value of p<0,05. SAAT amount present was bigger in women with obesity (p<0.0006). The fibroses between the deposits of SAAT and VAT was only observed among mulatto and black women with obesity (p<0,012). The amount of fibrosis in SAAT was not correlated to the variable clinics in women without obesity. However, with the ones undergoing bariatric surgery, it was observed correlations of fibrosis in SAAT with body mass index (BMI), glycated hemoglobin (A1c), LDL, triglycerides; and in VAT with the percentage of preoperative fat loss, percentage of total fat loss, percentage of pre lean mass, Basal Metabolic Rate (BMR) and Basal Energetic Consumption (BEC). The metabolic parameters and the anthropometric profile of the bariatric surgery were associated to the fibrosis in SAAT, while the post-surgery parameters were associated to the fibrosis in VAT.